Influence of incubation period, temperature and different phosphate levels on phosphate adsorption in soil - Rajput, A.; Panhwar, Qurban Ali; Naher, Umme Aminun; Rajput, S.; Hossain, E.; Jusop, Shamsuddin (Science Publications, 2014)
Phosphorus (P) is the most important element after nitrogen but P sorption properties are poorly documented in many soils. In this study, P sorption capacity in relation to incubation period and temperature under various P levels were determined for two different soil series (Rustam and Miani). Phosphorus was added at 5, 10, 25, 50, 100, 250, 500 and 1000 μg g-1 to the soils and incubated for the period of 1, 3, 7, 15, 30 and 60 days at 25 and 35±1°C temperatures. Phosphorus sorption was significantly influenced by the temperature, added P and incubation period. Clay content has major influence on P sorption. Rustum Series adsorbed more P than that of Miani Series. The P sorption was faster at high temperature (35°C). At the end of period in the Rustum Series with added 2.5 and 1000 μg g-1 P level, P sorption were found 0.7 and 943 μg g-1, respectively, at 25±1°C temperature, whereas at 35±1°C temperature the respective P sorption for same P levels were 1.8 and 987.0 μg g-1. In the Miani Series at 25±1°C temperature, P sorption was 0.7 and 941 μg g-1, while at the temperature of 35±1°C, P sorption were 1.0 and 986 μg g-1 soil. Increasing P levels, temperature and incubation, resulted in higher P sorption. Hence, high clay in combination with calcium carbonate contents enhanced P adsorption, while high organic matter and high native soil P resulted in lesser P adsorption.